A systemic Pasteurella multocida toxin aggravates cardiac hypertrophy and fibrosis in mice. (30th March 2015) - Weise, Markus; Vettel, Christiane; Spiger, Katharina; Gilsbach, Ralf; Hein, Lutz; Lorenz, Kristina; Wieland, Thomas; Aktories, Klaus; Orth, Joachim H. C.
Summary P asteurella multocida toxin (PMT) persistently activates heterotrimeric G proteins of the Gαq/11, Gα12/13 and Gαi family without interaction with G protein‐coupled receptors (GPCRs). We show that PMT acts on heart tissue in vivo and on cardiomyocytes and cardiac fibroblasts in vitro by deamidation of heterotrimeric G proteins. Increased normalized ventricle weights and fibrosis were detected after intraperitoneal administration of PMT in combination with the GPCR agonist phenylephrine. In neonatal rat cardiomyocytes, PMT stimulated the mitogen‐activated protein kinase pathway, which is crucial for the development of cellular hypertrophy. The toxin induced phosphorylation of the canonical phosphorylation sites of the extracellular‐regulated kinase 1/2 and, additionally, caused phosphorylation of the recently recognized autophosphorylation site, which appears to be important for the development of cellular hypertrophy. Moreover, PMT stimulated the small GTPases Rac1 and RhoA. Both switch proteins are involved in cardiomyocyte hypertrophy. In addition, PMT stimulated RhoA and Rac1 in neonatal rat cardiac fibroblasts. RhoA and Rac1 have been implicated in the regulation of connective tissue growth factor (CTGF) secretion and expression. Accordingly, we show that PMT treatment increased secretion and expression of CTGF in cardiac fibroblasts. Altogether, the data indicate that PMT is an inducer of pathological remodelling of cardiac cells and identifies the toxin as a promising tool for studying heterotrimeric G protein‐dependent signalling in cardiac cells.